A Continental Assessment of the Drivers of Tropical Deforestation With a Focus on Protected Areas - Fritz, Steffen; Laso Bayas, Juan Carlos; See, Linda; Schepaschenko, Dmitry; Hofhansl, Florian; Jung, Martin; Dürauer, Martina; Georgieva, Ivelina; Danylo, Olga; Lesiv, Myroslava; McCallum, Ian (Frontiers in Conservation Science, 2022)
Deforestation contributes to global greenhouse gas emissions and must be reduced if the 1.5° C limit to global warming is to be realized. Protected areas represent one intervention for decreasing forest loss and aiding conservation efforts, yet there is intense human pressure on at least one-third of protected areas globally (Jones et al., 2018). There have been numerous studies addressing the extent and identifying drivers of deforestation at the local, regional, and global level. Yet few have focused on drivers of deforestation in protected areas in high thematic detail. Here we use a new crowdsourced data set on drivers of tropical forest loss for the period 2008 to 2019, which has been collected using the Geo-Wiki crowdsourcing application for visual interpretation of very high-resolution imagery by volunteers. Extending on the published data on tree cover and forest loss from the Global Forest Change initiative (Hansen et al., 2013), we investigate the dominant drivers of deforestation in tropical protected areas situated within 30 degrees north and south of the equator. We find the deforestation rate in protected areas to be lower than the continental average for the Latin Americas (3.4% in protected areas compared to 5.4% in the Latin Americas) and Africa (3.3% compared to 3.9%), but it exceeds that of unprotected land in Asia (8.5% compared to 8.1%). Consistent with findings from foregoing studies, we also find that pastures and other subsistence agriculture are the dominant deforestation driver in the Latin Americas, while forest management, oil palm, shifting cultivation and other subsistence agriculture dominate in Asia, and shifting cultivation and other subsistence agriculture is the main driver in Africa. However, we find contrasting results in relation to the degree of protection, which indicate that the rate of deforestation in Latin America and Africa strictly protected areas might even exceed that of areas with no strict protection. This crucial finding highlights the need for further studies based on a bottom up crowdsourced, data collection approach, to investigate drivers of deforestation both inside and outside protected areas.